In silico investigation of new binding pocket for mitogen activated kinase kinase (MEK): Development of new promising inhibitors. (December 2015) - Yari, Hamed; Ganjalikhany, Mohamad Reza; Sadegh, Hamidreza
Graphical abstract: Highlights: A comprehensive in silico screening was done on MEK1/2 inhibitors. A training dataset was provided to be used for further related investigations. Trametinib was determined as the best provided inhibitor, so far. A set of 15 novel MEK1/2 inhibitors were designed in this study. Abstract: It has been previously shown that the inhibition of mitogen activated protein kinase kinase (MEK) contributes to apoptosis and suppression of different cancer cells. Correspondingly, a number of MEK1/2 inhibitors have been designed and evaluated since 2001. However, they did not satisfy essential pharmacokinetic (PK) and pharmacodynamic (PD) properties thus, almost most of them were terminated in pre-clinical or clinical studies. This study aims to design new specific MEK1/2 inhibitors with improved PK/PD profiles to be used as alternative cancer medications. In first part of this study, a comprehensive screening, for the first time, was done on well-known MEK1/2 inhibitors using a number of computational programs such as AutoDock Tools 4.2 (ADT) and AutoDock Vina. Therefore a valuable training dataset as well as a reliable pharmacophore model were provided which were then used to design new inhibitors. According to the results of training dataset, Trametinib was determined as the best inhibitor provided, so far. So, Trametinib was used as the lead structure to design new inhibitors in this study. In second part of this investigation, a set of new allosteric MEK1/2 inhibitors were designed significantly improving the binding energy as well as the ADMET properties, suggesting more specific and stable ligand-receptor complexes. Consequently, the structures 14 and 15 of our inhibitors, as the most potent structures, are great substituents for Trametinib to be used and evaluated in clinical trials as alternative cancer drugs.